A Study on the Chinese Translation of European Automobile Brand Names from the Perspective of Skopos Theory - Lin, Yuanhao (Asia Pacific Economic and Management Review, 2025)
Brand names are of great significance in reflecting the history and culture of their brands. Similarly, the translation of the name of an automobile brand profoundly affects its brand image, positioning and consumer acceptance, as well as the purchase price and consumers' willingness to buy. With the globalization of the automobile industry, the quality of a brand's translation has a direct impact on whether a European automobile manufacturer can successfully occupy a place in the Chinese market, therefore, effective translation of European automobile brands in the Chinese market is imperative. Successful Chinese translation is crucial for high sales of European car brands in China. The Chinese translation of the brand names has to be in accordance with the cultural psychology, customs and aesthetic interests of Chinese people. This study focuses on the application of skopos theory, aiming to explore how to translate European automobile brand names into Chinese using skopos theory through literature review and case study. It is found that European automobile brands mainly adopt the translation methods of literal translation, free translation and transliteration, which follow the principles of skopos, coherence and fidelity of the skopos theory.